EFFICACY OF CORPORATE ENVIRONMENTAL RESPONSIBILITY IN INDIA: AN ANATOMIZATION - Saha, Sohom; Das, Pradip Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Corporate firms have distinct responsibilities towards the planet. The responsibility towards the environment is one of the significant factors that needs to be appeased. In India, legislative intervention related to corporate social responsibility has been implemented, encompassing the environmental responsibilities of companies. However, it has remained one of the smallest fulfilled aspects of social responsibility. In this layout, corporate environmental responsibility requires a separate directive for enforceability. Various elucidations have been providing almost homogenous denotation on the environmental responsibility of companies. From ancient history to modern philosophy, the environmental responsibilities of persons have been advanced. Considerably, several directive measures have been provided, which have been followed by the merchants and companies, who are also following several existing legal provisions relating to environmental protection. Several global bodies provided enlightenment with respect to the environmental responsibility of companies. Supporting extracts of judicial precedents have been canvassed. Thus, an analysis is required to detect the extent of the existing legal provisions, which are lacking to fulfil the responsibility towards the environment. This investigation has covered all aspects related to the environment, as well as the responsibility of companies to assess the effectiveness of corporate environmental responsibility in India.